Sleep apnea detection with SMS notification - Julaihi, Farizzul; Jumadi, Nur Anida (Penerbit UTHM, 2020)
Sleeping is a process in which the body and mind is in recurring state. Sleeping is not only affecting human health but also can affect body mass index (BMI) and metabolic regulation of a person [1]. Sleep occurs in repeating periods, in which the body alternates between two distinct modes, rapid eye movement (REM) sleep and non-REM sleep [2]. During sleep, most of the body’s systems are in an anabolic state, which help to restore the immune, nervous, skeletal and muscular systems [3]. Human may suffer from various sleep disorders such as insomnia, hypersomnia and sleep apnea.